Gestión administrativa en la Gobernación de la Provincia de Los Ríos - Villalva Pacheco, Diana Magdalena (2022)
The Government of Los Ríos is a public institution whose labor competencies are destined to guarantee the security of the citizens, stable democratic processes and the correct development of the public institutions of the province through active surveillance. The objective of the research is to analyze the influence of administrative management on the development of labor competencies. The methodology is made up of the inductive method, because particular situations derived from administrative management were analyzed. The types of research were field and descriptive; While the techniques used are survey and interview, which allowed obtaining the following results: the management of human talent has erroneous behaviors and attitudes such as absenteeism or lack of punctuality, document management lacks speed and impacts on internal communication and Institutional planning has constant POA-PAC resolutions, in addition, there is an erroneous record of information in the SITAC due to processes with errors or omissions, and internal management has not implemented training processes to strengthen organizational weaknesses in the Los Ríos Government.